A study guide for the mastery of grammatical structures and the improvement of the english language learning with the students of the ninth year of basic education at “Manuel Cabrera Lozano” high school. Motupe extension. Academic year 2009 - 2010 - ORDÓÑEZ ARMIJOS, EDWIN (2011)
The following study guide named “A STUDY GUIDE FOR THE MASTERY OF GRAMMATICAL STRUCTURES AND THE IMPROVEMENT OF THE ENGLISH LANGUAGE LEARNING WITH THE STUDENTS OF THE NINTH YEAR OF BASIC EDUCATION AT “MANUEL CABRERA LOZANO” HIGH SCHOOL. MOTUPE EXTENSION. ACADEMIC YEAR 2009-2010. It is to help students with English grammar, to clarify some aspects that we considered important; when we are going to learn a foreign language. This study guide is to contribute with the English Teaching, with enough theoretical and grammar structures, practical exercises and vocabulary to improve the learning in the English Language Teaching-Learning Process. To elaborate the study guide we analyzed the grammar contents from the Our World Through English book Nº 2, the methods used during the elaboration were Direct Method to get a correct grammar and vocabulary, Natural Approach to know commands, games skits and small group work and Communicative Language Teaching to learn the meaning translation. Therefore we used different bibliographical material, to obtain the necessary grammatical information, and practical exercises. In the study guide there are seven units, each unit concentrates on a particular point grammar and uses, in the units there are explanations and examples; and exercises. At the back of the book there is a key for you check your answers to the exercises. With this study guide, we help to teachers, in the English Language teaching process, because there is a guide to improve the English Learning activities with the corresponding answers to all the grammar practice exercises to get a good students knowledge.